Legal problems with the transformation of waste into the products (a case study of phosphogypsum) - M. A. Buchakova; N. D. Vershilo; O. A. Dizer (Правоприменение, 2022)
The subject. One of the problems of contemporary states is waste and the search for opportunities for transformation into products. In this aspect, phosphogypsum, which is a waste product of mineral fertilizers, is interesting. It is subject to recycling in a small amount now.he purpose of the article is to identify legal possibilities for regulating relations related to industrial waste in terms of their secondary use.The main results, scope of application. Phosphogypsum can be used for the construction of highways, dams; the production of fertilizers and salts; the production of construction products using non-recycled phosphogypsum; agriculture; in the production of gypsum binders and products made from them; in the cement industry; as a filler in various industries. With the technological possibility of recycling such waste as phosphogypsum, there is no legal possibility of their use. The absence of the necessary legal regulation of relations in the field of waste disposal, clear legally fixed criteria for classifying waste as secondary material resources and the possibility of their use, may entail certain negative consequences for economic entities.Conclusions. The process of waste transformation into products from a legal point of view should consist of the following stages: waste disposal (both with and without pretreatment); the process of waste transformation into products directly (with a license for waste of hazard classes I – IV, compliance with licensing requirements, conclusion of the state environmental expertise on processing and disposal technologies, equipment used in this process, etc.). The following stage is legally correct and documented recognition of waste that is secondary material resources. The last stage is exclusion of said waste that is secondary material resources from approved waste generation standards and limits on their placement, as well as reflection of their movement in the journal of waste generation and movement.